Cytotoxicity of Two Bioactive Root Canal Sealers - Anja Baraba; Sonja Pezelj-Ribarić; Marija Roguljić; Ivana Miletić (University of Zagreb. School of Dental Medicine, 2016)
Objective: The aim of this study was to investigate the cytotoxicity of two different bioactive root canal sealers: one based on mineral trioxide aggregate, MTA Fillapex (Angelus, Solucoes Odontologicas, Londrina, PR, Brazil), and the other based on bioceramics, Endosequence BC Sealer (Brasseler, Savannah, Georgia, USA), in culture of mouse L929 fibroblasts. Materials and methods: Mouse fibroblasts (L929), obtained from subcutaneous connective tissue of mouse line C3Hf, were cultivated in plastic culture flasks in an incubator at 37ºC, with 5% CO2 and 90% humidity. Freshly mixed Endosequence BC Sealer and MTA Fillapex (0.1 g each) were placed on sterile teflon discs, 6 mm in diameter. Teflon discs with the materials as well as empty discs serving as control were placed in wells of 12-well plate. After incubation times of 1, 6, 20 and 24 hours, the teflon discs were removed from the wells and the number of viable cells was determined using trypan blue in Neubauer chamber. Results: In comparison to the control group, MTA Fillapex had significantly less viable cells for all incubation periods (p≤0.05), while Endosequence BC sealer had significantly less viable cells after 6, 20, and 24 hours of incubation (p≤0.05). MTA Fillapex exhibited ignificantly less viable cells in comparison to Endosequence BC sealer after the first hour and after 20 hours of incubation (p≤0.05), while for the other incubation periods there were no significant differences (p≥0.05). Conclusion: MTA Fillapex and Endosequence BC sealer were both cytotoxic in cultures of mouse L929 fibroblasts.